Performance and behavior of LLZO-based composite polymer electrolyte for lithium metal electrode with high capacity utilization. (November 2020) - Zhou, Dong; Zhang, Mengyi; Sun, Fu; Arlt, Tobias; Frerichs, Joop E.; Dong, Kang; Wang, Jun; Hilger, André; Wilde, Fabian; Kolek, Martin; Hansen, Michael Ryan; Bieker, Peter; et al.
Abstract: A thin membrane (≈47 μm) of a Celgard separator-reinforced cross-linked LiTFSI-PEO-Pyr14 TFSI-LLZO composite polymer electrolyte (CgCPE) was prepared and investigated for its ability to suppress the formation and propagation of high surface area lithium (HSAL) with dendritic morphology. The membrane shows superior cycling stability in Li||Li-symmetric cells under high capacity utilization (5 mAh/cm 2 ) for up to 2000 h. Using a combination of conventional laboratory techniques and nondestructive synchrotron X-ray tomography, the synergetic effect of the membrane components towards homogenous lithium electrodeposition/dissolution was revealed. The modulated ion migration in CgCPE and decreased interfacial/interphasial resistance ensures an evenly regulated Li-ion flux during deposition. While, the good mechanical properties of the CgCPE membrane were maintained up to a capacity utilization of 15 mAh/cm 2 . Based on the results, an approach for a hybrid solid electrolyte to control lithium electrodeposition for Li metal electrodes with high capacity utilization is provided, and furthermore, such an approach could be further used for lithium metal batteries with high energy density and safety. Graphical abstract: Image 1 Highlights: A 47 µm CgCPE membrane (Celgard-reinforced cl-PEO-LiTFSI-Pry14 TFSI-LLZO) was characterized with Li metal electrode. EXSY NMR indicates an exchange of Li ions between the LiTFSI and LLZO species in the complex CgCPE membrane. Good cycling stability was shown in Li||Li-symmetric cells at 5 mAh/cm2 charge/half cycle for 2, 000 hours. Synchrotron X-ray tomography was used to investigate the morphological evolution at the Li metal electrode|CgCPE interface. The synergetic effect between the CgCPE components affects the Li ion flux for a more homogeneous Li electrodeposition.